KUALITAS PELAYANAN PUBLIK PADA KANTOR POS CABANG PASANGKAYU 91571: KUALITAS PELAYANAN PUBLIK PADA KANTOR POS CABANG PASANGKAYU 91571 - Septiawan Ardiputra; Muhammad Rizky Prawira (stiatabalong.ac.id, 2020)
Pasangkayu Branch Post Office 91571 is one of the work units of PT.Pos Indonesia (Persero) whose working area covers 12 Districts in Pasangkayu Regency. Pasangkayu Branch Post Office 91571 as a public organization is required to be able to meet customer needs as service users by providing quality public services. If this is done with continuous improvement efforts according to customer needs, it will have an impact on meeting customer satisfaction. This study aims to analyze the quality of public services at the Pasangkayu 91571 Post Office. This research uses qualitative research. Data collection techniques in research using techniques: observation, interviews and documentation. Data were analyzed using data reduction techniques, data presentation and drawing conclusions. The results showed that the quality of public services at the Pasangkayu 91571 Post Office has not been maximally implemented because it has not fulfilled customer satisfaction in providing postal services. This is evidenced by the 5 indicators that are used as benchmarks in the study, there is one focus of the study that is not fulfilled, namely the indicators of physical evidence (tangible) where there are inadequate service waiting room facilities so that customers feel uncomfortable waiting in line. The four other indicators, namely reliability, responsiveness, assurance, and empathy (empathy) have supported the maximum quality of service at the Pasangkayu 91571 Post Office. Keywords : keywords assurance, empathy, reliability, responseveness, tangibles.